Adenocarcinoma of the female urethra: a case report - José de Carvalho Neto; Sydney C. Leão; Ricardo Fakhouri; Roberto Gurgel; Julia Maria G. Dias; Nivaldo F. Vieira
ABSTRACT The urethral adenocarcinoma is a rare malignant tumor that affects predominantly women. Its incidence is higher after the age of 50 in this group. The knowledge about this disease is limited due to its low frequency and is mainly based on case reports. Although rarely presenting distant metastasis, the clinical consequences of treating this condition may bring an important negative impact on patient's quality of life. This is mainly due to mutilating surgery and the need to use permanent urinary catheter. It is presented a case report of a patient with urethral adenocarcinoma and its therapeutic management.